Using Causality to Infer Coordinated Attacks in Social Media - Manchanayaka, Isura; Zaidi, Zainab Razia; Karunasekera, Shanika; Leckie, Christopher (Proceedings of the International AAAI Conference on Web and Social Media, 2025)
The rise of social media has been accompanied by a dark side with the ease of creating fake accounts and disseminating misinformation through coordinated attacks. Existing methods to identify such attacks often rely on thematic similarities or network-based approaches, overlooking the intricate causal relationships that underlie coordinated actions. This work introduces a novel approach for detecting coordinated attacks using Convergent Cross Mapping (CCM), a technique that infers causality from temporal relationships between user activity. We build on the theoretical framework of CCM by incorporating topic modelling as a basis for further optimizing its performance. We apply CCM to real-world data from the infamous IRA attack on US elections, achieving F1 scores up to 75.3% in identifying coordinated accounts. Furthermore, we analyse the output of our model to identify the most influential users in a community and uncover leader-follower dynamics based on inferred causal relationships. We also demonstrate how our method reveals coordinated behaviour across different time periods, including campaigns predating the 2016 elections. We apply our model to a case study involving COVID-19 anti-vax related discussions on Twitter. Our results demonstrate the effectiveness of our model in uncovering causal structures of coordinated behaviour, offering a promising avenue for mitigating the threat of malicious campaigns on social media platforms.